Adenosine-Induced NLRP11 in B Lymphoblasts Suppresses Human CD4+ T Helper Cell Responses - Irem Ozel; Ilgin Akkaya; Ece Oylumlu; Goksu Uzel; Ceren Ciraci (Journal of Immunology Research)
NLRP11 is a member of the PYD domain-containing, nucleotide-binding oligomerization-domain (NOD-) like receptor (NLR) family. The true stimulus of NLRP11 is still unclear to date, so the current study is built upon NLRP11 induction via adenosine stimulation and that activation can shape adaptive immune responses in a caspase-1-independent manner. We examined the regulation and mechanism of adenosine responsiveness via NLRP11 in human Daudi Burkitt’s B lymphoma cells and their effects on human peripheral CD4+ T lymphocytes from healthy individuals. NLRP11 was significantly upregulated after induction with adenosine at both the mRNA and protein levels, which led to the interaction of endogenous NLRP11 with the ASC adaptor protein; however, this interaction did not result in the activation of the caspase-1 enzyme. Furthermore, cocultures of NLRP11-expressing Burkitt’s lymphoma cells and naïve human peripheral CD4+ T lymphocytes had reduced IFN-γ and IL-17A production, whereas IL-13 and IL-10 cytokines did not change. Interestingly, IFN-γ and IL-17A were recovered after transfection of Burkitt’s lymphoma cells with siRNAs targeting NLRP11. Concomitant with NLRP11 upregulation, we also exhibited that adenosine A2B receptor signaling induced two phosphorylated downstream effectors, pErk1/2 and pAkt (Ser473), but not pAkt (Thr308). Taken together, our data indicate that adenosine is a negative regulator of Th1 and Th17 responses via NLRP11 in an inflammasome-independent manner.